Evolution of white dwarf stars with high-metallicity progenitors: The role of 22Ne diffusion - Althaus, Leandro Gabriel (2010)
Motivated by the strong discrepancy between the main-sequence turnoff age and the white dwarf cooling age in the metal-rich open cluster NGC 6791, we compute a grid of white dwarf evolutionary sequences that incorporates for the first time the energy released by the processes of 22Ne sedimentation and of carbon/oxygen phase separation upon crystallization. The grid covers the mass range from 0.52 to 1.0M⊙, and is appropriate for the study of white dwarfs in metal-rich clusters. The evolutionary calculations are based on a detailed and self-consistent treatment of the energy released from these two processes, as well as on the employment of realistic carbon/oxygen profiles, of relevance for an accurate evaluation of the energy released by carbon/oxygen phase separation. We find that 22Ne sedimentation strongly delays the cooling rate of white dwarfs stemming from progenitors with high metallicities at moderate luminosities, while carbon/oxygen phase separation adds considerable delays at lowluminosities. Cooling times are sensitive to possible uncertainties in the actual value of the diffusion coefficient of 22Ne. Changing the diffusion coefficient by a factor of 2 leads to maximum age differences of ≈8%-20% depending on the stellar mass. We find that the magnitude of the delays resulting from chemical changes in the core is consistent with the slowdown in the white dwarf cooling rate that is required to solve the age discrepancy in NGC 6791.